Does Foreign Market listing results into Greater Foreign Institutional Ownership and Better Market Co-Integration: Evidence from Indian Companies listed on New York Stock Exchange - Himanshu Joshi and Vinay Dutta (Abhigyan, 2011)
It is believed that foreign listing of the securities enhances liquidity of a company‟s stock on account of greater capital market interaction between domestic country and the foreign country where the shares are traded. Greater capital market interaction can take place in two ways. First, companies may cross list in the foreign capital market as Global Depository Receipts (GDRs) and American Depository Receipts (ADRs) and choose one of the foreign stock exchanges as their primary listing exchange. Second, foreign institutional investors can invest in these companies in market around the world. For present study, we have taken 10 reputed Indian companies which are listed on US stock exchange (NYSE). When companies list on U.S exchanges, they have to follow the stock exchanges and SEC requirements on disclosure. While there are many disclosure exemptions for foreign companies from the domestic rules, the level of disclosure required is generally quite high. Managers of these companies may voluntarily increase disclosure in domestic market to attract foreign institutional investors. Thus we predict that foreign market listing increases domestic voluntary disclosure which attract higher foreign institutional ownership and may result into greater co-integration between share prices of these companies in domestic and foreign stock exchanges. For the purpose of present study we have used Transparency and Disclosure survey developed by Standard and Poor‟s.